Dunlap, "Inherited Silence: Listening to the Land, Healing the Colonizer Mind" - Garcia, Ivis (The Trumpeter, 2024)
Louise Dunlap's book "Inherited Silence: Listening to the Land, Healing the Colonizer Mind" is a heartfelt exploration of the historical harm caused by colonization, with a focus on Dunlap's Californian roots. Through a blend of personal experiences and broader themes such as climate change, resource wars, and genocide, Dunlap offers insight into the trauma caused by colonization and suggests self-healing strategies for descendants. The book is split into ten chapters, each of which explores a different aspect of the issue.